Factors Of Tripartite Consultation Influencing The Performance Of State Corporations In Kenya - Nzioki, Susan (My University, 2013)
This study sought to establish the factors of tripartite consultation that influenced the performance of state corporations in Kenya. Kenya has one of the oldest institutions for tripartite consultation and social dialogue in Africa, but the established mechanism had not been used with degree of consistency. Hence, the benefits of tripartism had not been reaped. The study adopted a descriptive survey design. The population of the study constituted all the state corporations in Kenya and the target population comprised the unionized state corporations in Nairobi County. Fourteen state corporations were randomly selected from which study subjects were drawn. Stratified random and purposive sampling were applied. The research instruments included questionnaire and interview guide. Quantitative and qualitative data were analyzed by use of Statistical Package of Social Sciences (SPSS) and establishment of emerging themes respectively. The study found that employers adequately performed their roles. Besides, trade unions had adequately performed their roles but had not assured workers a share of profits and had not publicized the Charter. Besides, the Ministry of Labour had played its roles amidst challenges among others, delay in settlement of disputes, human resource constraints and inadequate budgetary allocations. The tripartite consultation system existed but had challenges such as reluctance of trade unions recognition, delay in conclusion and implementation of collective agreements. Economic change had insignificant effect on performance of state corporations since, the government cushioned the corporations in hard economic times. Besides confrontational approach had been embraced by most strong trade unions as the most effective approach of solving labour issues like pay. Tripartite consultation positively intervened between the independent variables and the dependent variable. The study adopted two multiple linear regression models. One with and the other without the effect of the intervening variable. When tripartite consultation was held constant, all the variables had significant positive effect on the performance of state corporations, apart from economic change. With effect of tripartite consultation, it was found that all the variables had significant positive effect on the performance of state corporations apart from relationship between social partners and economic change. Some of the study's recommendations included: government should enhance the capacity of the Ministry of Labour; future negotiations should be informed by research that takes into account increase in production. The study suggested the following areas for future research: investigate on HRM Union Substitution/ suppression in non-unionized state corporations and effects of economic change on the performance of the private sector companies in Kenya.